MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN JIGSAW SISWA KELAS XI MIPA I SMAN 6 MERANGIN - Sufriati (Mat-Edukasia, 2021)
The purpose of this study was to describe the increase in mathematics learning outcomes using the jigsaw learning model. The type of research used is classroom action research using the Jigsaw Learning model. The subjects of this study were 32 students of class XI MIPA I SMA Negeri 6 Merangin in the academic year. The data collection technique is to do a final test in each cycle and observations are made during the learning process. Based on the learning outcomes test that has been carried out, the information on the average value of 64.5 in the first cycle became 83.43 in the second cycle, an increase of 18.93. For the percentage of students who complete the KKM 9 people (28.125%) in the first cycle to 29 people (90.625%) in the second cycle or an increase of 62.5%. Student activity has increased, in cycle I the average student activity 45.51% increased in cycle II to 85.31% or an increase of 39.8%. Based on this, it can be concluded that the use of the jigsaw learning model can improve student learning outcomes and activities.